Factors Causing the Poor Management of Village-Owned Enterprises (BUMDes) in Garut Regency - A.Ikeu Kania (Jurnal Manajemen Indonesia, 2020)
The management of BUMDes in Garut Regency is still not in accordance with the mandate of the laws and regulations that its establishment is intended to create and to improve the prosperity of rural community life better through mobilization and management of village potential. This study aims to discover the factors that cause the low management of BUMDes in Garut Regency. Using a quantitative approach, the survey was conducted toward BUMDes management who are in the categories of semi-active and not yet active. A total of 161 respondents were selected by a simple random sampling method which was further analyzed using exploratory factor analysis with 32 indicators. The results showed that of the 32 indicators tested, 8 new factors are formed as factors that lead to poor management of BUMDes in Garut Regency. These factors include management, human resources, environmental conditions, personality, organization, policy, professionalism and communication. Keywords: Management, Exploratory Factor Analysis, BUMDes, Rural Community